MULTI CRITERION PRIORITY ON KRIGING OF GOLD RESOURCES PREDICTION - Amri, Nur Ali; Bargawa, Waterman Sulistyana; Cahyadi, Tedy Agung (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
This paper describes of three things. First, the Kriging estimation on gold grade which is distributed in the vein. The empirical variogram method based on Matheron classical and robust of Cressie-Hawkins. The two empirical fitting on variogram theory of spherical and exponential equations of weighted least squares and ordinary least squares used. The predictions of six sizes block-Kriging respectively, 15×15, 25×25, 35×35, 50×50, 75×75 and 100×100 based on four variographic models. Second, determine the priority of 24 prediction combinations based on TOPSIS method. Finally, the multiple criterion decision making method namely, 15×15 block Kriging based on a robust empirical variogram of exponential weighted least squares model represents as the best result.